2002
DOI: 10.1113/jphysiol.2002.023333
|View full text |Cite
|
Sign up to set email alerts
|

Placental glucose transport in growth-restricted pregnancies induced by overnourishing adolescent sheep

Abstract: Glucose clamp procedures were used to determine whether the slowing of fetal growth during the final third of gestation in overnourished adolescent ewes is due to a reduction in placental glucose transport capacity. Singleton pregnancies to a single sire were established by embryo transfer and thereafter adolescent dams were offered a high (n = 11) or moderate (n = 7) nutrient intake. Studies were conducted at 130 +/- 0.5 days gestation. Uterine and umbilical blood flows were studied by the steady-state transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 20 publications
5
46
0
Order By: Relevance
“…This approach was critical to determine the basis of the previously observed changes in placental development and function in late gestation. The study demonstrated that placental mass per se is not perturbed by maternal overfeeding until sometime during the final third of pregnancy and as such confirms previous studies in which the pregnancies were terminated at single points coincident with either mid (Wallace et al 2004b or late (Wallace et al 2000(Wallace et al , 2002a(Wallace et al , 2002b gestation. Moreover, the data revealed for the first time that the fetuses of overnourished dams may be initially on a higher growth trajectory than control fetuses between day 50 and 90 of gestation, with fetal weight being 11% greater by day 90 in the H group.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…This approach was critical to determine the basis of the previously observed changes in placental development and function in late gestation. The study demonstrated that placental mass per se is not perturbed by maternal overfeeding until sometime during the final third of pregnancy and as such confirms previous studies in which the pregnancies were terminated at single points coincident with either mid (Wallace et al 2004b or late (Wallace et al 2000(Wallace et al , 2002a(Wallace et al , 2002b gestation. Moreover, the data revealed for the first time that the fetuses of overnourished dams may be initially on a higher growth trajectory than control fetuses between day 50 and 90 of gestation, with fetal weight being 11% greater by day 90 in the H group.…”
Section: Discussionsupporting
confidence: 76%
“…Although cellular proliferation within the fetal cotyledon was only marginally influenced by maternal diet at day 50 of gestation, we did observe a significant reduction in the vascular development within the fetal cotyledon at this early stage. The reductions in capillary area density and area per capillary (i.e., vessel size) in the overnourished dams may explain the previously reported reductions in uterine blood flow in mid-gestation (Wallace et al 2008a) and in uteroplacental blood flows and nutrient uptakes in late gestation (Wallace et al 2002a(Wallace et al , 2002b(Wallace et al , 2003a in this experimental paradigm. The mechanism underlying this nutritionally-mediated alteration in vascular development is unknown.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…In general, the size of the placenta is correlated with its glucose and amino acid transfer capacity, which is determined by transporter abundance (reviewed by Regnault et al (2005) and Fowden et al (2006c)). Interruptions in the normal placental growth trajectory caused by carunclectomy (Owens, et al, 1987), heat stress (Thureen et al, 1992), nutrition manipulation (Wallace et al, 2002), or prolonged hypoglycemia (Carver and Hay, 1995) may either increase or decrease glucose and amino acid transporter abundance and hence, the efficiency of placental nutrient-transfer capacity.…”
Section: Placental Formationmentioning
confidence: 99%